Case Studies in Operations Research Applications of Optimal Decision Making - Murty, Katta G.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This textbook is comprised of detailed case studies covering challenging real world applications of OR techniques. Among the overall goals of the book is to provide readers with descriptions of the history and other background information on a variety of industries, service or other organizations in which decision making is an important component of their daily operations. The book considers all methods of optimum decision making in order to improve performances. It also compares possible solutions obtained by different approaches, concluding with a recommendation of the best among them for implementation. By exposing students to a variety of applications in a variety of areas and explaining how they can be modeled and solved, the book helps students develop the skills needed for modeling and solving problems that they may face in the workplace. Each chapter of "Case Studies in Operations Research: Applications of Optimal Decision Making" also includes additional data provided on the book$1 (Bs website on Springer.com. These files contain a brief description of the area of application, the problem and the required outputs. Also provided are links to access all the data in the problem. Finally there are project exercises for students to practice what they have learnt in the chapter, which can also be used by instructors as project assignments in their courses.s
Intelligent Modeling Essential to Get Good Results: Container Storage Inside a Container Terminal -- Diesel Locomotive Fueling Problem (LFP) in Railroad Operations -- Organizing National Elections in India to Elect the 543 Members of the Lok Sabha -- Procurement, Production, Marketing at Supply-Driven Milk and Milk Products Co-Operative -- DSS (Decision Support System) for Allocating Appointment Times to Calling Patients at a Medical Facility -- Transportation-Location Problem for a Solar Stove Distributing Nonprofit Organization -- Designing Earth Dams Optimally -- Optimal Scheduling of a Multi-Unit Hydro-Power Station in a Short-Term Planning Horizon -- Optimizing the Design of Water Distribution Networks Using Mathematical Optimization -- Wood Inventory Management in the Paper Industry -- Optimizing the Design of Heat Exchanger Networks in Crude Oil Refineries -- Optimizing the Allocation of Cuboidal Boxes to Cuboidal Compartments for Storage in a Warehouse -- Optimal Intake and Routing of Floating Oil Rigs in the North Sea -- Addressing the Peak Power Problem Through Thermal Energy Storage -- Optimal Flight Planning for a Jet Aircraft -- Freight Transport By Rail -- Cutting Stock Problems in the Paper and Sheet Metal Industries -- Inventory Management in Blood Banks -- Assembling Cells in the Wet Cell Traction Batteries that Power Forklifts -- Giving Appointments to Patients for Surgeries and Scheduling Surgeries to Operating Rooms in a Day -- The Satellite Downlink Scheduling Problem: A Case Study of RADARSAT-2 - Problem Statement and Data Files -- An Integer Programming Model for the Ferry Scheduling Problem - Online Summary With Data Files.
Keywords: Economics; Operations research; Economics/Management Science; Operation Research/Decision Theory; Operations Research, Management Science